ChemInform Abstract: Catalysis by Lithium Perchlorate Enables Double‐Conjugate Addition of Electron‐Deficient Maleimides to 2‐Aminopyridines and 2‐Aminothiazoles. Issue 5 (13th February 2013) - Matviiuk, Tetiana; Gorichko, Marian; Kysil, Andriy; Shishkina, Svitlana; Shishkin, Oleg; Voitenko, Zoia
Abstract Lithium perchlorate is found to catalyze the conjugate addition of maleimides (II) to 2‐aminopyridines or 2‐aminothiazoles.